2019
DOI: 10.1016/j.mjafi.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing gastro-laryngeal tube with endotracheal intubation for airway management in patients undergoing ERCP under general anaesthesia

Abstract: Background: Gastro laryngeal tube (GLT) is a newly introduced device. It is an advanced purpose specific design (essentially a modified laryngeal tube) which especially provides a separate wide channel specifically designed for the introduction of a gastroscope for endoscopic retrograde cholangio-pancreatography (ERCP), simultaneously functioning as a supra-glottic airway device for ventilation. Methods: In a randomized controlled trial on 100 patients undergoing ERCP under GA, GLT was compared with endotrache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Inflammatory bowel disease is a group of chronic non-specific intestinal diseases with an unclear aetiology, and the onset age tends to be younger. 14 Patients are prone to disease uncertainty in the face of repeated conditions, complex treatment, adverse drug reactions, impaired cognition and confusion about the development and outcome of the disease. Disease uncertainty interferes with patients’ ability to obtain information about the condition and impacts their psychological well-being, treatment confidence and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease is a group of chronic non-specific intestinal diseases with an unclear aetiology, and the onset age tends to be younger. 14 Patients are prone to disease uncertainty in the face of repeated conditions, complex treatment, adverse drug reactions, impaired cognition and confusion about the development and outcome of the disease. Disease uncertainty interferes with patients’ ability to obtain information about the condition and impacts their psychological well-being, treatment confidence and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…in their study reported the successful use of GLT in Indian patients. [20] However, stress response to GLT has not been studied till now, even though stress response to other supraglottic airways such as LMA and laryngeal tube have been documented. [71521]…”
Section: Discussionmentioning
confidence: 99%